A 10 year follow up study of patients transplanted for autoimmune hepatitis: histological recurrence precedes clinical and biochemical recurrence. Issue 6 (1st June 2003) - Duclos-Vallée, J-C; Sebagh, M; Rifai, K; Johanet, C; Ballot, E; Guettier, C; Karam, V; Hurtova, M; Feray, C; Reynes, M; Bismuth, H; Samuel, D
Abstract : Background and aim: Autoimmune hepatitis (AIH) has been reported to recur after orthotopic liver transplantation (OLT) in 10–35% of patients in small series with a short follow up. The aim of the present study was to examine the clinical and histological outcome more than 10 years after OLT for AIH. Patients and methods: Seventeen women with a mean age of 30 (12) years at the time of OLT, selected from among 44 patients transplanted for AIH, were followed for more than 10 years. The criteria for definite AIH, as established by the International Autoimmune Hepatitis Group, were met in every case. Liver biopsies were performed 1, 2, 5, and 10 years after OLT, and when indicated by abnormal liver function tests. Specimens were examined for evidence of recurrent AIH, namely interface hepatitis, lobular activity, portal lymphoplasmocytic infiltration, and fibrosis. Other signs of recurrence included hypertransaminasaemia, serum autoantibodies, and the response to steroid reintroduction or significant steroid dose increments. Results: AIH recurred in 7 (41%) of 17 patients. In four patients histological abnormalities were detected by means of protocol biopsies 1–5 years before the onset of biochemical abnormalities. Two patients developed severe recurrences after 10 and 15 years, respectively, and required treatment with steroids and tacrolimus. In the other three patients histological recurrence was detected 0.6–3 years post-OLT, concomitantly with biochemical abnormalities. Conclusions: AIH recurred in 41% of patients followed for more than 10 years after OLT. As histological signs preceded biochemical abnormalities in four patients (23.5%), regular liver biopsy is warranted after OLT. Detection of isolated histological signs may call for closer follow up and/or a change in immunosuppressive therapy.